Simulation of IGBT Based Cyclo-Inverter Run Induction Motor - Govind, Sudhin; Thomas, Jiku (Asian Journal of Electrical Sciences, 2013)
This paper introduces a new technique for converting power at supply frequency to a higher frequency, using a cyclo-inverter circuit, where IGBT is used as the switching element. This circuit is used in induction heating, ballast, high frequency supplies and in high speed induction motors. The control circuit developed for the cyclo-inverter supplies trigger signals for the IGBT for developing power at any frequency which is an integer multiple of supply frequency. The high frequency power is then used to run a single phase capacitor start induction motor for developing high speeds. The working of the proposed system was verified by observing waveforms on CRO and was found to be satisfactory.